PENGARUH AUDIT KEWASPADAAN STANDART TERHADAP TINGKAT KEPATUHAN KEBERSIHAN TANGAN PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT ISLAM MALANG UNISMA - DENA DARA JATI; FRENGKI APRYANTO; ROSLY ZUNAEDI (LPPMK STIKES Widyagama Husada, 2023)
Background: Compliance with hand washing in hospitals is still a problem. Even in the Islamic Hospital of Malang UNISMA has not yet reached 100%, even though according to the Health Accreditation Standards team it 100%. Objective: The purpose of this study was to determine the effect of audits on the level of adherence to hand hygiene by nurses. Method: This study used a pre-experimental design with a one group pre-post test design approach and purposive sampling. The research instrument was an audit observation sheet and SOP for Hand Hygiene. The number of respondents was 55 nurses using the paired-t statistical test to determine the effect of the audit on the level of adherence to nurse's hand hygiene. Results: Before the audit the results were 78.2%, after the audit was carried out 81.8% of the nurses complied with the moment of hand washing and 65.5% complied, before the audit of the SPO of hand washing was carried out, after the audit 100% complied. There is a significant influence between the two variables (p=0,001) Conclusion: There is an influence on the level of compliance with nurse's hand hygiene. Suggestion: Hospital are expected to carry out audits in accordance with established policies in order to discipline nurses to carry out hand washing according to the SPO. Nurses are expected to increase awareness and discipline towards hand hygiene compliance.